High statistics study of in-medium S- and P-wave quarkonium states in lattice Non-relativistic QCD - Kim, Seyong; Petreczky, Peter; Rothkopf, Alexander (Nuclear physics. A, Nuclear and hadronic physics, 2017)
Many measurements of quarkonium suppression at the LHC, e.g. the nuclear modification factor RAA of J/Ψ, are well described by a multitude of differen…